2017
DOI: 10.21037/jtd.2017.04.29
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors in the evaluation of treatment response to neoadjuvant chemoradiotherapy in patients with advanced esophageal squamous cell cancer

Abstract: Neoadjuvant therapy before esophagectomy is evidence-based, and is a standard-of-care for locally advanced and operable esophageal cancer. However response to such treatment varies in individual patients, from no clinical response to pathological complete response. It has been consistently shown that a good pathological responses is of prognostic value, but perhaps in the expense of those who do not. It is important to identify suitable predictive factors for response, so that patients are not exposed to poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…However, this survival advantage (9% at five years) [ 6 ] is not due to an incremental improvement in outcome for all patients, but instead driven by a very good response in less than 20% of patients treated with the ECX regimen [ 7 , 8 , 9 , 10 , 11 ], or in 37% of patients treated with the FLOT regimen [ 11 ]. Primary tumor regression following neoadjuvant therapy (NAT) can be measured using the Mandard Tumor Regression Grade (TRG) in resected specimens after surgery [ 12 , 13 , 14 ] and is informative for both disease-free and overall survival [ 13 , 14 , 15 ]. A Mandard TRG score of 1 corresponds to complete regression of the tumor leaving only fibrosis; TRG 2 is defined by fibrosis and scattered residual tumor cells; TRG 3 and 4 display progressively less tumor regression; and TRG 5 tumors display no regressive changes in response to NAT [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this survival advantage (9% at five years) [ 6 ] is not due to an incremental improvement in outcome for all patients, but instead driven by a very good response in less than 20% of patients treated with the ECX regimen [ 7 , 8 , 9 , 10 , 11 ], or in 37% of patients treated with the FLOT regimen [ 11 ]. Primary tumor regression following neoadjuvant therapy (NAT) can be measured using the Mandard Tumor Regression Grade (TRG) in resected specimens after surgery [ 12 , 13 , 14 ] and is informative for both disease-free and overall survival [ 13 , 14 , 15 ]. A Mandard TRG score of 1 corresponds to complete regression of the tumor leaving only fibrosis; TRG 2 is defined by fibrosis and scattered residual tumor cells; TRG 3 and 4 display progressively less tumor regression; and TRG 5 tumors display no regressive changes in response to NAT [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this survival advantage (5% at 5 years) (Smyth et al 2017) is not due to an incremental improvement in outcome for all patients, but instead driven by a very good response in less than 20% of patients (Noble et al 2017; Sjoquist et al 2011). Primary tumor regression following neoadjuvant therapy (NAT) can be measured using the Mandard Tumor Regression Grade (TRG) in resected specimens after surgery (Mandard et al 1994; Tan et al 2016; Tao et al 2015) and is informative for both disease-free and overall survival (Wong and Law 2017; Tan et al 2016; Tao et al 2015). Genetic mechanisms associated with tumor response to NAT have been assessed in a variety of different cancer types (Chakiba et al 2014; Cramer et al 2018; Greenbaum et al 2019; Höglander et al 2018; Lesurf et al 2017; Li et al 2020; Zhu et al 2020) including rectal adenocarcinoma, but have not been widely investigated in EAC.…”
Section: Introductionmentioning
confidence: 99%
“…Neoadjuvant chemotherapy, which is also known as initial chemotherapy, refers to the reduction of tumor size through chemotherapy before surgery, this can reduce tumor load and control distant metastasis as early as possible. Existing studies have shown that preoperative neoadjuvant chemotherapy can significantly improve the shortterm and long-term survival rate of patients [48,49]. Fluorouracil and paclitaxel combined with platinum and platinum, respectively, are two commonly used chemotherapy regimens for esophageal cancer [49].…”
Section: Adjuvant Therapy and Neoadjuvant Therapymentioning
confidence: 99%
“…Existing studies have shown that preoperative neoadjuvant chemotherapy can significantly improve the shortterm and long-term survival rate of patients [48,49]. Fluorouracil and paclitaxel combined with platinum and platinum, respectively, are two commonly used chemotherapy regimens for esophageal cancer [49]. Stiles et al [50] reviewed the survival status of 238 patients who received neoadjuvant therapy or chemotherapy and radiotherapy before resection during 1987-2013.…”
Section: Adjuvant Therapy and Neoadjuvant Therapymentioning
confidence: 99%